An Immunomodulatory Gallotanin-Rich Fraction From Caesalpinia spinosa Enhances the Therapeutic Effect of Anti-PD-L1 in Melanoma - Lasso, Paola; Gomez-Cadena, Alejandra; Urueña, Claudia; Donda, Alena; Martinez-Usatorre, Amaia; Romero, Pedro; Barreto, Alfonso; Fiorentino, Susana (Frontiers in Immunology, 2020)
PD-1/PD-L1 pathway plays a role in inhibiting immune response. Therapeutic antibodies aimed at blocking the PD-1/PD-L1 interaction have entered clinical development and have been approved for a variety of cancers. However, the clinical benefits are reduced to a group of patients. The research in combined therapies, which allow for a greater response, are strongly encouraging. We previously characterized a polyphenol-rich extract from Caesalpinia spinosa (P2Et) with anti-tumor activity in both melanoma and breast carcinoma, as well as immunomodulatory activity. We hypothesize that the combined treatment with P2Et and anti-PD-L1 can improve the antitumor response through an additive antitumor effect. We investigated the antitumor and immunomodulatory activity of P2Et and anti-PD-L1 combined therapy in B16-F10 melanoma and 4T1 breast carcinoma. We analyzed tumor growth, hematologic parameters, T cell counts, cytokine expression and T cell cytotoxicity. In the melanoma model, combined P2Et and anti-PD-L1 therapy has the following effects: decrease in tumor size; increase in the number of activated CD4+ and CD8+ T cells; decrease in the number of suppressor myeloid cells; increase in PD-L1 expression; decrease in the frequency of CD8+ T cell expressing PD-1; improvement in the cytotoxic activity of T cells; and increase in the IFN secretion. In the breast cancer model, P2Et and PD-L1 alone or in combination shows antitumor effect with no clear additive effect. This study shows that combined therapy of P2Et and anti-PD-L1 can improve antitumor response in a melanoma model by activating the immune response and neutralizing immunosuppressive mechanisms.